Influence of Ag nanoparticles on the physical properties of multilayers of graphene - Jose Edgar Alfonso; John Jairo Olaya (Dyna, 2019)
Graphene has attracted considerable interest due its exceptional physical properties. This article describes the thermoelectric and magnetic properties such as the Seebeck coefficient and the magnetoresistance, at room temperature, of multilayers of graphene fabricated through the chemical vapor deposition (CVD) method and coated with Ag nanoparticles (NPs). According to the results, the Seebeck coefficient increased from -30 to -5 μV/K as a function of deposition time of Ag NPsand magnetoresistance increase their initial value as a function of sheet resistance up to 16.6%.